How Perceived Organizational Support Shapes Employee Engagement: Evidence From Healthcare Professionals in a Regional Public Hospital - Karima Astari; Ilham Medal Junjunan; Fanisa Megawati Subagio (Psychosocia : Journal of Applied Psychology and Social Psychology, 2026)
Hospital management requires professionals from various disciplines who are able to collaborate in providing quality, effective, efficient, and responsive healthcare services according to patient needs. Medical and health personnel are key elements in determining the success of these services. Their optimal contribution will be achieved if they have high employee engagement. One factor related to employee engagement is Perceived Organizational Support (POS). This study aims to analyze the relationship between POS and Employee Engagement among medical and health personnel at Bandung City Regional General Hospital. The study used a quantitative approach with a cross-sectional design. Of the 260 questionnaires collected, 236 responses were declared valid and analyzed after a data screening process. Data collection used the POS Scale and Employee Engagement, which have been tested for reliability. The results of a simple linear regression analysis showed that POS had a positive and significant relationship with Employee Engagement (β = 0.749, t(234) = 15.09, p < 0.001). The overall regression model was significant, F(1,234) = 227.79, p < 0.001, with a Adjusted R² = 0.559, indicating that 55.9% of the variance in Employee engagement can be explained by POS. This finding indicates that POS is an important predictor of work engagement in the context of a public hospital with high workloads and limited resources. Practically, hospital management needs to prioritize fair policies, transparency of the system provided, and strengthening supervisor support to improve the perception, support, and engagement of medical and health personnel.